Social Inequalities in ELT Classroom and Challenges on Teachers - Kandel, Ganesh Kumar (Journal of NELTA Karnali, 2022)
This paper analyzes the policies and pedagogies related to English language teacher education (ELTE) in Nepal. Similarly, this study also addresses issues of social equalities and inequalities associated to ELT, Challenges that English language teachers are facing due to these social inequalities in the classroom, and the role and action that teachers can perform to mitigate these inequalities. From the review of different sources, it was found out that there exist various forms of social inequities in the English language teaching (ELT) classroom which have created several challenges for teachers in the classroom. Moreover, this study suggests that although avoiding social inequalities is tough work, the teachers can perform several actions and avoid social inequalities if they really show their commitment to solve the issue and take action accordingly.